Web Usability of Public Organization Websites: The Case of Indonesian Ministry Websites - ROKHMAN, ALI; SATYAWAN, DARMANTO (Jurnal Studi Pemerintahan, 2012)
As a consequence of the development of Information and Communication Technologies (ICT),nowadays almost all governments around the world, included Indonesian government have officialwebsites to provide information and services for their citizen. In the second period of PresidentSusilo Bambang Yudhoyono administration has thirty two ministries and each ministries have anofficial website. However implementation of the ministry websites have not been measured yet onusability aspect. The objective of this research is to examine the usability of ministry websites ofIndonesian Government. Eleven websites was taken as sample in this study. Respondents are 128Internet users who have competency for assessing web usability. Usability of websites weremeasured by several indicators were adapted from E-Government Toolkit for Developing Countriesthat was prepared by the National Informatics Centre and UNESCO. The main indicators consistof navigation architecture, layout design, and content.